Effect of systemic high dose enzyme replacement therapy on the improvement of CNS defects in a mouse model of mucopolysaccharidosis type II. Issue 1 (December 2015) - Cho, Sung Yoon; Lee, Jeehun; Ko, Ah-Ra; Kwak, Min Jung; Kim, Sujin; Sohn, Young Bae; Park, Sung Won; Jin, Dong-Kyu
Abstract Background Mucopolysaccharidosis type II (MPS II, Hunter syndrome), is caused by a deficiency of iduronate-2-sulfatase (IDS). Despite the therapeutic effect of intravenous enzyme replacement therapy (ERT), the central nervous system (CNS) defects persist because the enzyme cannot cross the blood-brain barrier (BBB). There have been several trials of direct infusion to the cerebrospinal space showing promising results; however, this approach may have limitations in clinical situations such as CNS infection. The objective of this study was to improve the CNS defect with systemic high-dose ERT. Methods Systemic ERT was performed using three doses (1, 5, and 10 mg/kg weekly) of IDS for three different durations (1, 3, and 6 months) in IDS knock out (KO) mice of two age groups (2 months, 8 months). GAG measurement in tissues, brain pathology, and behavioral assessment were analyzed. Results Brain IDS activities increased in parallel with the concentrations of IDS injected. The glycosaminoglycan (GAG) level and histopathology in the brains of the young mice improved in a dose- and duration-dependent manner; however, those were not improved in the old mice, even at higher doses of IDS. The spontaneous alternation behavior was recovered in young KO mice treated with ≥ 5 mg/kg IDS; however, no significant improvement was observed in old KO mice. Conclusions These results suggest that high-dose ERT given to mice of earlier ages may play a role in preventing GAG accumulation and preventing CNS damage in IDS KO mice. Therefore, ERT above the present standard dose, starting in early childhood, could be a promising treatment regimen for reducing neurological impairment in Hunter syndrome.